Issues of restricting the constitutional rights of the individual when authorizing the arrest of property by the investigating judge - Kulbayeva М.М. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2021)
In the article, the author analyzes the norms of the current legislation about restrictions on the constitutional rights of the individual when the investigating judge authorizes such a measure of procedural coercion as the seizure of property. There were studied statistical data on the consideration by investigating judges of applications for the authorization of the seizure of property and the amount of compensation for the established amount of material damage. The article investigates the determinants of the tendency to increase the total amount of compensation for material damage caused by a crime in comparison with the previous period. In addition to the level of inflation, the author has evaluated the coronavirus pandemic, the effectiveness of the investigative courts. The author substantiates the conclusion that it is necessary to introduce into the national legislation of the Republic of Kazakhstan recommendations for its improvement, based on the judicial precedents of the European Court of Justice in cases of seizure of property. It is noted that it is necessary to regulate a separate procedural order of the seized property, which has specific features. In addition, proposals are made to resolve other issues presented in the article.